Kinetic controlled affinity labeling of target enzyme with thioester chemistry. Issue 15 (1st August 2016) - Tomohiro, Takenori; Nakabayashi, Masahiro; Sugita, Yuka; Morimoto, Shota
Graphical abstract: A ligand probe containing thioester linkage enabled specific labeling of target protein that is rapidly progressing reaction. Abstract: High specificity has been an important feature in affinity labeling for target profiling. Especially, to label targets via rapidly progressing reactions with consumption of ligand (probe), high specificity of reaction with common functional groups of target protein should be achieved without reactions with similar groups of non-target proteins. Herein, we demonstrate the kinetic controlled affinity labeling of acyl CoA synthetase using a fatty acid analogue containing a phenylthioester linkage. High specificity was attained by accelerating the labeling rate in the binding pocket. This approach could be useful for profiling a series of target enzymes and transporters in signal transduction pathways.